Dimensions of macroeconomic uncertainty: A common factor analysis - Steffen Henzel; Malte Rengel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
In the current literature uncertainty about the future course of the economy is identified as a possible driver of business cycle fluctuations. In fact, uncertainty surrounds the movements of all economic variables which gives rise to a monitoring problem. We identify the different dimensions of uncertainty in the macroeconomy. To this end, weconstruct a large dataset covering all forms of economic uncertainty and unravel the fundamental factors that account for the common dynamics therein. These common factors are interpreted as macroeconomic uncertainty. Our results show that the first factor captures business cycle uncertainty while the second factor is identified as oil and commodity price uncertainty. Finally, we demonstrate that a distinction between both types of macroeconomic uncertainty is essential since they have rather different implications for economic activity.
Keywords: C32; C38; E32; 330; Macroeconomic uncertainty; factor model; factor-augmented VAR; aggregate fluctuation